The Influence of Internal Control Systems, Accounting Information Systems and Human Resources Competencies on the Quality of Financial Reports: Pengaruh Sistem Pengendalian Internal, Sistem Informasi Akuntansi dan Kompetensi Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan - Wulandari, Rachma Dwi; Abidin, Fityan Izza Noor (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to demonstrate the impact of internal control systems, accounting information systems, and employee skills on the quality of financial reporting in a tulangan county cooperative. This research method adopts quantitative method. All stables in the fortified area were the population in this study, and the sampling technique used intentional sampling. Meanwhile, he received a sample of 60 respondents. The use of data in raw form was achievied by distributing questionnaires directly to officers or managing directors in the tulangan district. In this study the method multiple linear regression analysis was used with the help of the SPSS 26 program. The results of this study show that : the internal control system has a significant impact on financial quality information with a significant value of 0,000. Accounting information systems have a significant impact on financial quality of information with a significant score of 0,004. And with a significant value of 0,005, the competence of personnel has a significant effect and is significant on the quality of financial reporting.